T-fuzzy multiply positive implicative BCC-ideals of BCC-algebras - Jianming Zhan; Zhisong Tan (International Journal of Mathematics and Mathematical Sciences)
The concept of fuzzy multiply positive BCC-ideals of BCC-algebras is introduced, and then some related results are obtained. Moreover, we introduce the concept of T-fuzzy multiply positive implicative BCC-ideals of BCC-algebras and investigate T-product of T-fuzzy multiply positive implicative BCC-ideals of BCC-algebras, examining its properties. Using a t-norm T, the direct product and T-product of T-fuzzy multiply positive implicative BCC-ideals of BCC-algebras are discussed and their properties are investigated.